DESTINATION BRANDING CAPABILITY AND BEACH TOURISM PATRONAGE IN AKWA-IBOM STATE, NIGERIA - Joseph Sunday Etuk (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Gaining and sustaining appreciable level of tourists’ patronage is a difficult and challenging task for some tourist destinations in Akwa- Ibom. This study evaluated the effect of destination branding capability on the patronage of tourist beaches, based on the perspectives of beach tourists/visitors in Akwa-Ibom State, Nigeria. Descriptive survey research design was adopted for the study. The population of the study comprised of domestic and foreign tourists at 4 beaches) in Akwa Ibom State during the 2019 Christmas and New year holiday from which a sample of 323 visitors was drawn using Freud and Williams formula for sample size determination from an infinite population. Primary data were collected from a well-structured questionnaire and administered on the visitors/tourists at four beaches in Akwa Ibom State, and secondary data from academic journal papers, textbooks, and internet resources. Statistical tools for data analyses include; descriptive analysis, Exploratory Factor Analysis (EFA), Principal Component Analysis (PCA) and, Regression Analysis. The findings of the descriptive analysis revealed destination deficiencies in experiential and cultural differentiations as low patronage of the beaches. The study concludes that destination branding capability had a significant positive effect on tourist satisfaction but insignificant effect on revisit intention. Based on the results of the study, it was recommended adequate tourism funding by that Akwa Ibom State Ministry of Tourism and Culture and to come up with beach concept, design and pictorial images for the beaches as well as focusing its destination branding campaign on experiential differentiation that projects a memorable and satisfying experience for sun, sand and sea (beach) tourists.